Sociology of Individual Voluntary Tax Compliance - Subramaniam, Muthaloo; Vaicondam, Yamunah; Nadarajan, Dineswary; Lai Leng, Yap (International Journal of Psychosocial Rehabilitation, 2020)
Taxation plays an important role in any country. It is not only contributes towards the wealth of the nation but interestingly the health of the nation. Wealth comprises of contribution to the sources of revenue and distribution of revenue to the good use for the nation. The nation will prosper and having healthy lifecycle will eventually benefit its citizen at large. In 2001, Malaysia went to through transition from Official Assessment System (OAS) to Self- Assessment System (SAS). It is a system that allow the taxpayers to calculate their own tax liability within the boundaries of tax laws. It was different previously where the determination of tax liability, calculation and other tax administrative works lie greatly with Inland Revenue Board of Malaysia (IRBM). Managing own tax matters are known as voluntary tax compliance and this relieves the tax authorities from great deal of resources. The study is aimed to investigate the ethical, moral, religious and cultural background considerations on individual voluntary tax compliance whose main income is from doing business. This is a quantitative study. Total of 230 questionnaires distributed to respondents and 87% of the questionnaires returned with total number of valid 200 responses. Necessary tests including multiple regression analysis were used in this study. Findings showed that ethicality and religiosity have direct significant effect on the individual tax compliance among the taxpayers whose main income from doing business. However, morality and cultural background do not have significant effect in this relationship. It was believed this study will significantly contributes to the body of knowledge in the areas of voluntary tax compliance.